Formation of Physical Culture in the High School Students on the Basis of Reflexive Approach - Askarov Fakhritdin (Genius Publishing Group, 2023)
This article discusses the formation of the physical culture of high school students on the basis of the reflexive approach. In the process of physical culture, the needs for physical exercises, the corresponding value orientations, beliefs and habits are formed. The reflexive approach contains large reserves of a unique and productive approach to improving the educational process not only in the subject "Physical Education", but also in many others at all levels of the functioning of the education system
Keywords: lesson; teacher; high school students; reflexive approach